Enhancing the Capacity of MSMEs through Social Media and Financial Literacy Training in Sulaman and Silver Cici Koto Gadang - Anas, Yulia; Oktavia, Fitriyeni; Afifah Usman, Nurul; Amelia, Novi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Training in social media and financial literacy is crucial for enhancing the capabilities of micro, small, and medium-sized enterprises (MSMEs), especially traditional craft businesses like Sulaman and Silver Cici Koto Gadang MSME. The objective of this study is to examine the impact of these training programs on attitude formation, subjective norms, and perceived behavioral control, as outlined by the Theory of Planned Behavior (TPB). Through a qualitative approach involving participatory observation, in-depth interviews, and pre- and post-tests, the study reveals significant improvements in participants' ability to manage digital marketing and understand financial risks, particularly concerning illegal online loans. The results suggest that positive attitudes toward social media as a strategic marketing tool are emerging, along with a deeper understanding of financial management and the identification of illegal lending practices. Stronger perceived behavioral control, as demonstrated by increased post-test scores, encourages MSMEs to adopt safer financial practices and sustain digital marketing efforts. Overall, this study confirms that integrated interventions are effective. These interventions combine digital skills training and financial literacy. They effectively strengthen MSME resilience and competitiveness in the digital economy.